2003
DOI: 10.1021/la026498v
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Antibody Orientation on Charged Self-Assembled Monolayers

Abstract: The orientation of antibodies on surfaces is critical to the performance of biosensors. Due to the charge distribution within an antibody molecule, it is hoped that the orientation of adsorbed antibodies can be controlled by adjusting microenvironments (e.g., surface and solution properties). In this work, we investigated the orientations of two types of monoclonal anti-human chorionic gonadotropin (anti-hCG) adsorbed on NH2 (positively charged) and COOH (negatively charged) terminated self-assembled monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
231
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(248 citation statements)
references
References 39 publications
(71 reference statements)
14
231
1
Order By: Relevance
“…Differences in adsorption and or CE due to pH value variation are clear indicators of electrostatic forces and physical adsorption (Chen et al 2003). For this experiment (Fig.…”
Section: Effects Of Buffer Ph On the Cementioning
confidence: 80%
See 2 more Smart Citations
“…Differences in adsorption and or CE due to pH value variation are clear indicators of electrostatic forces and physical adsorption (Chen et al 2003). For this experiment (Fig.…”
Section: Effects Of Buffer Ph On the Cementioning
confidence: 80%
“…The lowest pH (pH 5) resulted in the lowest CE. A possible explanation might be the positive charge of the applied antibodies at pH 5 and the assumption that antibodies bind stronger to negatively charged surfaces at lower ionic strength with head-on orientation rather than with end-on orientation, thus resulting in lower reactive particles (Chen et al 2003). At pH 6, a small percentage of polyclonal antibodies exhibits isoelectric behaviour, so that hydrophobic forces exceed the electrostatic ones.…”
Section: Effects Of Buffer Ph On the Cementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Chen et al [24] showed that the orientation of adsorbed anti-hCG can be controlled by appropriately tuning the microenvironments of the adsorption process (i.e., surface and solution properties). The IEP of anti-hCG (pH 6.8) lies between those of its F(ab') 2 (pH 8.5) and F c (pH 6.1) fragments.…”
Section: Probing Protein Orientation On Charged Surfacesmentioning
confidence: 99%
“…The use of Id specific peptide as molecular probe could highly improve affinity and selectivity of the capture surface. In addition, it simplifies the biochip functionalization procedure with respect to that employed for antibodies in which controlling protein orientation is still very challenging [19]. In this setting, we constructed an Id-peptide-based biosensor by using as substrate both planar and porous silicon.…”
Section: Introductionmentioning
confidence: 99%